Experimental and Numerical Analysis of Shear Performance of 16 m Full-Scale Prestressed Hollow Core Slabs - Kang Zhao; Hui Wang; Houchuan Li; Yang Wei; Jinwei Lu; Guofen Li (Infrastructures)
To investigate the shear performance of 16 m span prestressed hollow core slabs, shear tests were conducted on three pre-tensioned prestressed hollow core slabs with the same shear-to-span ratio. A systematic analysis was performed on the failure modes, crack development patterns, load–deflection relationships, and load–strain relationships of the prestressed hollow slabs. The test results indicate that all specimens experienced shear-compression failure under the same shear-to-span ratio (2.71). The main diagonal shear cracks were distributed within a range of 1.35 m to 1.95 m from the beam ends, with crack angles approximately between 45° and 55°. Finite element software ABAQUS was used for detailed numerical simulation of the tests. By comparing the failure modes and load–displacement curves, the reliability and applicability of the finite element model were verified.